The Student’s Self-Designed Learning Activities Influencing Their Learning Achievement: A Case Study of an English Tutorial Center in Krabi - Ariyawong, Onnicha; Phongsatha, PhD, Thanawan (ABAC ODI JOURNAL Vision. Action. Outcome, 2017)
The implementation of the “self-designed learning activities” method in fifteen secondary school students who were conveniently selected at an English tutorial center in Krabi has been explored. The investigation was carried out by employing the pretest and post-test to determine the level of their knowledge prior to and after implementing self-designed activities. The observation during 36 hours classroom participation had been recorded to see levels of their skills improvement. The questionnaires were used to identify a level of students’ perceptions towards the program whether it is statistically significantly different from the neutral level (3.42). The results revealed that the post-test score was higher than the pretest . The number of students who had generally improved those skills was greater during classroom observation. In addition, the students rated their perceptions towards self-designed learning activities at 4.45, which was statistically significantly higher than the value of 3.42 as hypothesized. It can be concluded that the self-designed learning activities effectively help to enhance students’ learning interests as well as their performance in the subject matter. These findings are also particularly relevant and beneficial to teachers and facilitators as the teaching designers who design the lesson plan in order to increase students’ learning achievement.